PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN ADMINISTRASI UMUM KELAS X DI SMKN 1 PADANG PANJANG - Ranti Novira; Marwan Usman; Oknaryana Oknaryana (Jurnal Ecogen, 2018)
This study aims to improve students learning outcomes in the subjects of General Administration by using cooperative learning model type make a match in class X Automation and Office Administration (OTP) 2 in SMKN 1 Padang Panjang. This type of research is a classroom action research with Arikunto action research model, which is implemented on two cycles, namely cycle I and cycle II. Subjects in this study were students of class X Automation and Office Adminstration (OTP) 2 in SMKN 1 Padang Panjang year lesson 2017/2018 consisting of 32 students. Data collection technique is to use test result of cognitive domain in the form of objective test. Based on the results of research, obtained average learning outcomes General Administration subjects in the first cycle is 76.88 with the percentage of students mastery is 62.5%. While the average learning outcomes obtained in the second cycle is 77.38 with the percentage of students mastery is 78.13%. So it can be argued that student learning outcomes with the application of cooperative learning model type make a match on the subjects of General Administration class X in SMKN 1 Padang Panjang is increasing. And it is advisable to teachers in SMKN 1 Padang Panjang should use cooperative learning model type make a match as a model of learning that can be used in the process of learning General Administration because it can improve student learning outcomes. Keyword: Cooperative Learning, Type Make A Match, Learning Outcomes